PENGGUNAAN REGISTER DALAM WACANA RESEP MASAKAN BLUE BAND - Afsari, Asri Soraya (JURNAL PESONA, 2018)
AbstractOn its using, language has diverse variation. Language in formal situation will be different from the informal one. Likewise the language for advertisement is different from scientific paper. In Sociolinguistics, the application of a language variant is called as Register. The food recipe discourse is one type of the register for it has specific characteristics in particular grammar and structure. This writing tries to review the application of the register in Blue Band Â food recipe discourse. The result of the research indicates that it comprises vocabularies, morphology of derivatives and phrases, and also clauses. The finding register shows ingredients, tools, processing, and, serving.Keyword: register, food recipe discourse, sociolinguistics, vocabulary, morphology